Demographic Profile of COVID-19 Cases: Laboratory Experience in a Tertiary Care Hospital of Dhaka City - Khan, Tarek Mahbub; Afroz, Fatima; Mohiuddin, GM; Farzana, Aleya; Ashrafi, Fahmida; Tangim, Shaharat Farha; Farzana, Farah; Hossain, Enamul; Huda, SM Nazmul; Paul, Shikha (Sir Salimullah Medical College Journal, 2022)
Background: COVID-19 pandemic becomes a great threat due to continuous rise of the global incidence and emergence of multiple waves of infections in many countries of the world. The diversity of this infection varies from country to country and knowledge regarding demographic characteristics of this infection is essential to combat the pandemic situation. Objective: The aim of this study was to characterize the demographic profile of rRT-PCR (real time reverse transcriptase-polymerase chain reaction) confirmed COVID-19 cases and to provide a timeline regarding rates of infection. Materials and methods: This cross- sectional study was conducted at the Department of Virology of Sir Salimullah Medical College, Dhaka, Bangladesh from May, 2020 to April, 2021. rRT-PCR test was performed to detect SARS-COV2 in 35001 clinical samples and their demographic characteristics were analyzed. Results: Out of 35001 suspected cases,5008 (14.3%) were tested positive of which 58.0% belongs to the age group between 18–45 years.The majority of the cases were male (69.0%). Most of the positive cases became negative (85.0%) within three weeks of infection by rRTPCR test. The highest percentage (29.2%) of confirmed COVID-19 cases was reported in the month of May 2020, then gradual decrease in the subsequent months followed by a sharp rise to 27.2% in the month of March, 2021. Conclusion: This study shows an overall 14.3% positivity among suspected COVID-19 cases where adult males between 18-45 years are more commonly suffered. However, most of the infected persons become rRT-PCR negative within three weeks’ time. A second surge of SARS-COV2 infection has been documented in this study that coincided with second wave of COVID-19 in Bangladesh. Sir Salimullah Med Coll J 2022; 30: 9-13